Handbook of Emergency Ophthalmology (Springer International Publishing, 2018)
This book provides emergency physicians with an easy-to-use guide for diagnosing and treating ophthalmologic conditions in the emergency department. Ophthalmologic complaints are very common, but many emergency physicians are not as confident as they would like to be when evaluating and managing these conditions. This book answers that need by giving step-by-step instructions on how to diagnose and treat common eye conditions, including glaucoma, infections, neuro-ophthalmologic conditions, and trauma. For each disorder, the book discusses presentation/symptoms, physical examination techniques, lab and imaging findings, differential diagnoses, treatment guidelines, and referral suggestions. The text is filled with images that clearly present these common ophthalmologic complaints and conditions and guide the emergency physician to an accurate and swift diagnosis. Handbook of Emergency Ophthalmology is an essential resource for emergency physicians, residents, medical students, nurses, and other healthcare workers who evaluate and manage patients with ophthalmologic conditions.